Fuel Cells - Drillet, Jean-Francois; Du, Yanhai; Kolisnychenko, Stanislav (Specialized Collections, 2020)
The presented collection "Fuel Cells" consists of some selected proceedings papers published by Trans Tech Publications Inc. within the 2017 - 2019 period. It includes a wide range of engineering solutions and results from scientific research activities in the fuel cells area. Fuel Cells, Proton Exchange Membrane (PEM), Electrodes, Zirconate Ceramics, Interconnection, Solid State Electrolyte, Solid Oxide Fuel Cells (SOFC), Polymer Electrolytes, Yttria Stabilized Zirconia, Sealing, Joining Interface, Bipolar Plate, Ferritic Stainless Steel, Heat Exchanger, Nafion, Nanocomposites, Catalysts, Polymer Electrolyte Membrane, Hydrogen, Cationic Membranes, Diffusion, Proton Exchange Membrane Fuel Cell (PEMFC), Direct Methanol Fuel Cell (DMFC), Microbial Fuel Cell (MFC), Water Splitting, Hydrogen Production, Electrolyser, Power Supply System Materials Science, Mechanical Engineering, Manufacturing.